Biochar and/or Compost Applications Improve Soil Properties, Growth, and Yield of Maize Grown in Acidic Rainforest and Coastal Savannah Soils in Ghana - Albert Kobina Mensah; Kwame Agyei Frimpong (International Journal of Agronomy)
Use of biochar for soil fertility improvement is gaining popularity due to its potential to improve soil quality, increase crop yield, and sequester carbon from the atmosphere-biosphere pool into the soil. A 40-day pot experiment was carried out to investigate the effects of corncob biochar and compost applied alone (at a rate of 2%, w/w) or in combination (1% of each, thus 1% compost + 1% biochar) on soil physicochemical properties, growth, and yield of maize on two soils of contrasting pH and texture collected from the Rainforest and Coastal Savannah agroecological zones of Ghana. Biochar and compost applied alone or in combination significantly increased soil pH, total organic carbon, available phosphorus, mineral nitrogen, reduced exchangeable acidity, and increased effective cation exchange capacity in both soils. Additionally, combined application and single application biochar or compost additions increased the plant height, stem girth, and dry matter yields of two maize (local (“ewifompe”) and hybrid (Obaatanpa)) varieties used in the study. The study showed that biochar applied alone or in combination with compost offers the potential to enhance soil quality and improve maize yield.